Surgical Intervention in Upper Lid Haemangioma To Prevent Amblyopia: Two Cases Report - Sudjatmiko, Gentur; Marita, Adinda (Lingkar Studi Bedah Plastik Foundation, 2012)
Non-operative treatment for Hemangioma involving deeper skin structures extending into the mucosa is usually unsuccessful, since usually no involution will develop. Early surgical planning is important to prevent amblyopia and for the child’s self confidence of their cosmetic appearance later in life. We present two cases of superior palpebra hemangioma who underwent early surgical treatment. The first case involves a large hemangioma of the left superior palpebra with severe vision restriction; although later examination was proven that the visual function was still preserved. The second case involves a smaller perioccular lesion. Surgery was performed on both cases. In the larger hemangioma, only partial of tumor was removed by incision at the lid crease and intra-lesion injection of corticosteroids was administered to the remaining tumor.Advantages of surgical procedure in early rapidly growing stage and in very large hemangioma of upper eyelid; firstly, provides a definitive early treatment; secondly, safe because bleeding was manageable, and third prevent occlusion-related amblyopia. Besides these bene!ts surgery promises added esthetic outcome.